Peranan Kepala Sekolah dalam Mengoptimalkan Profesionalisme Guru di MI Ngaliyan Boyolali - Wulandari, Anis, Dra. Risminawati, M.Pd (2017)
The background of this research is the principal has the duty and responsibility to improve the quality of schools perform its role in optimizing the profesionalism of teacher in schools. The purpose of this study is to describe the role of the principal, to describe efforts of principal, to know the obstacles, and to know the solutions done by the principals in optimizing professionalism of teachers in MI Ngaliyan. The research type is field research with scriptive and qualitative analysis, and the data is collected by observation, interview, and documentation. The subjects in this study are the principal and teachers of MI Ngaliyan. Data analysis techniques used in this study are the data reduction, data display, and verivication.The results of this study indicate that:(1) the principal's role in MI Ngaliyan that is implemented are the role of educator, manager, administrator, supervisor, leader, innovator, and motivator. However, the implementation was limited by the facilities and infrastructures so that the performance is less optimal; (2) the efforts of the principal in optimizing the profesionalism of teachers in MI Ngaliyan are: ervising, breefing, optimizing the role of administrator, sending some teachers to attend the workshops and training; (3) the acles faced by the principal in optimizing the ssionalism of teachers in MI Ngaliyan include: the different character of teachers, limited facilities and nfrastructure, and the limited space; (4) the principal solution to overcome this obstacle is to: conduct regular meetings, alternately using the infrastructure, such as using LCD or projector, room utilization.Key words: principal, teacher's professionalism